AL Muqābalatu fī Kitābi Ihyā’i ‘Ulumi al Dīni (Dirāsatun Taḥlīliyyatun fī ‘Ilmi al Badī’i) - Lenisar, Lenisar; Fahri, Ismail (Al-Uslub: Journal of Arabic Linguistic and Literature, 2022)
This study aims to describe and find out (1) the types of muqobalah "in the book of ihya' ulumuddin" (2) the wisdom contained in the muqabalah sentence. This research is library research because the primary data and secondary data are books or related documents. This study uses a qualitative descriptive technique through a badi science approach. The results of the study are as follows. (1) The results of reading the first volume of the book Ihya 'Ulumuddin which is carried out in the sentence the author uses a lot of words that are opposite 2 or more words in the sentence. (2) in the book of Ihya 'Ulumiddin there are 5 types of muqabalah, namely: 2 to 2 muqabalah: 16, 3 to 3 as much: 5, 4 to 4 as much: 6, 6 to 5 as much, 1, 6 to 6 as much, 3.